2014
DOI: 10.1098/rsbl.2013.0870
|View full text |Cite
|
Sign up to set email alerts
|

The corn snake yolk sac becomes a solid tissue filled with blood vessels and yolk-rich endodermal cells

Abstract: The amniote egg was a key innovation in vertebrate evolution because it supports an independent existence in terrestrial environments. The egg is provisioned with yolk, and development depends on the yolk sac for the mobilization of nutrients. We have examined the yolk sac of the corn snake Pantherophis guttatus by the dissection of living eggs. In contrast to the familiar fluid-filled sac of birds, the corn snake yolk sac invades the yolk mass to become a solid tissue. There is extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…These hatchlings contrast markedly with the small aquatic larvae that commonly emerge from amphibian eggs. However, the macrolecithal condition of reptiles also required a series of mechanisms by which yolk nutrients could be processed for embryonic use (Elinson, ; Elinson & Stewart, ). In amphibians, cleavage is holoblastic, and yolk material lies within each of the dividing blastomeres from early stages of development onwards.…”
Section: Introductionmentioning
confidence: 99%
“…These hatchlings contrast markedly with the small aquatic larvae that commonly emerge from amphibian eggs. However, the macrolecithal condition of reptiles also required a series of mechanisms by which yolk nutrients could be processed for embryonic use (Elinson, ; Elinson & Stewart, ). In amphibians, cleavage is holoblastic, and yolk material lies within each of the dividing blastomeres from early stages of development onwards.…”
Section: Introductionmentioning
confidence: 99%
“…The yolk material itself is an extracellular liquid that is contained within the extraembryonic “yolk sac”. This yolk sac must somehow absorb and digest the yolk and send its products to the embryo to fuel its development (Elinson and Stewart, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations on the corn snake Pantherophis guttatus (Colubridae) have revealed a pattern of yolk sac development that is dramatically different from that of birds (Elinson and Stewart, ; Elinson et al., ; Powers and Blackburn, ). This pattern results in conversion of the yolk material into vascularized, spaghetti‐like strands of yolk‐filled cells.…”
Section: Introductionmentioning
confidence: 99%
“…That may not be the case. Elinson and Stewart (2014) recently reported that the yolk sac of the corn snake (Pantherophis guttatus) (Colubridae) eventually becomes a mass of spaghetti-like blood vessels coated by large endodermal cells (Fig. 1).…”
Section: B a B C A Yolk Sacs In Reptiles 891mentioning
confidence: 99%
“…A recent discovery that the yolk of the corn snake, Pantherophis guttatus, becomes cellularized and forms a solid, vascularized tissue (Elinson and Stewart, 2014) reveals a dramatic contrast to the development of the yolk sac of the chicken that raises questions regarding appropriate models for the egg of early amniotes. We will consider the relevance of development of the corn snake yolk sac to other squamates, and amniotes generally, and suggest a new scenario for the evolution of the yolk sac of oviparous amniotes.…”
Section: Introductionmentioning
confidence: 99%